Peran Profesi Akuntansi dalam Penerapan Cyber Security pada Sistem Akuntansi - Annisa Rizkyta Yulie; Mukhtaruddin . (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2026)
Transformation in digital technology have transformed contemporary accounting through automated and integrated cloud-based accounting systems to support increased efficiency and superior quality of financial reporting. However, this innovation also introduces cybersecurity risks threats affecting the privacy, integrity, and accessibility of financial reporting. This article examines the role of the accounting profession in managing cybersecurity risks in digital accounting systems and its implications for organizational governance and accountability. The method uses a Systematic Literature Review to review and analyze relevant articles from national and international journals. The findings indicate that technological complexity, weak technology-based internal controls, and limited digital competency increase system vulnerability. The accounting profession plays a role as a risk monitor, internal control designer, and information security evaluator to protect the integrity of financial data. This article emphasizes the need for enhanced digital competency, alignment of risk management activities and strengthening governance to ensure a secure, transparent, and accountable digital accounting system.